BALANCING ACTS: UNVEILING SOCIO-ECONOMIC AND ENVIRONMENTAL DIMENSIONS OF WASTE-TO-ENERGY POLICIES IN INDONESIA - Maddi, Maddi - (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
Rapid population increase, coupled with increasing urbanisation and industrialisation, is expected to create substantial demand for waste-to-energy (WtE) facilities in Indonesia. While the Indonesian government is working towards proper and economic handling of waste, there is a need to move beyond traditional incineration processes to more advanced WtE technologies in order to mitigate the adverse environmental impact. Along with this, a proper waste sorting system also needs to be established to improve the functioning of WtE facilities. However, challenges persist, including high capital costs, limited waste feedstock availability, and social acceptance concerns. Additionally, worries have been raised regarding the environmental and health impacts of WtE facilities, particularly their potential emissions of pollutants such as dioxins and furans. Overall, while WtE holds the potential to contribute to sustainable waste management and renewable energy development in Indonesia, careful planning and management are essential to ensure environmental, social, and economic sustainability. This study employs the Policy Effectiveness Assessment, guided by the Policy Implementation Theory, to evaluate WtE policies in Indonesia. By examining the intersection of environmental sustainability and socio-economic factors, the article aims to provide valuable insights into the effectiveness of current WtE policies. Through combining environmental, socio-economic, and technological perspectives, the article strives to offer a nuanced understanding of the challenges and opportunities, paving the way for informed policy decisions and sustainable waste management practices in the country.